COMPARATIVE STUDY OF LEAF TRICHOME IN DIVERSE HABIT OF SOME CASSIA SPECIES - SWATI J. JANE,; SUPRIYA D. WAGHMARE, (The Bioscan, 2025)
Epidermal trichomes areoften seen in the surface view of the leaf lamina. They are diverse structure and functions. Trichome plays crucial role in the identification of plantsThey may be unicellular or multicellular and are further classified on the basis of absence or presence of glands.They aredefendant for plants against plant against natural hazards such as herbivores, plants from extreme high or low temperature, drought, ultraviolet (UV) radiations, pathogen attacks andreduce excessive transpirationWang et, al. (2021).In the present study 6 Species belonging to the genusCassia were selectedit include two herb speciesC.absus L.,C. uniflora Mill., inshrub C.occidentalis L., C. alata L. and in tree C. siamea Lamk.,C. surattensis Burm. In these species diversity of trichomes,their structuralmorphological differences were studied.This review provides reference towards Taxonomic, Anatomical Study, Phylogeny and relationship among species of Cassia genus.